Концепт "ярмарок" в українській сміховій культурі - Бибик, С. (Культура слова, 2019)
У статті проаналізовано прозові твори ХІХ – ХХ століть, у яких представлено словесні картини ярмаркового середовища. Концепт «ярмарок» змодельовано на матеріалі мови художніх творів Г. Квітки-Основ’яненка, І. Нечуя-Левицького, С. Руданського, О. Вишні. Подано реалізацію в них кількох субконцептів: ярмарок як скупчення; ярмарок як галас; ярмарок як живомовна стихія; ярмарок і «низова» словесність; ярмарок як розвага. Об’єктами аналізу стали лексика і фразеологія відповідних контекстів, а також стилістичні прийоми створення ярмаркового гумористичного колориту. Виділено кілька різновидів текстів фольклору (або фольклоризованих текстів), які використовують письменники як засоби стилізації живомовної стихії на ярмарках в Україні, а також увиразнення різноманіття соціально-культурних масок, представлених на них (продавець, жид, циган, сліпий музикант, прохач, картяр тощо). Наголошено на тому, що концепт «ярмарок» у відповідних текстах оповідань зберігає ознаки бурлеску і просвітництва. ﻿The article analyzes prose works of the 19th – 20th centuries, presenting verbal pictures of the fair environment. The concept of «fairs» is modeled on the material of the language of works of art by G. Kvitka-Osnovianenko, I. Nechui-Levytskii, S. Rudanskii, O. Vishnia.Several subconcepts have been implemented in them: fair as a cluster; fair as a voice; fair as a living element; fair and grassroots literature; fair as entertainment. The objects of analysis were the vocabulary and phraseology of the respective contexts, as well as stylistic techniques for creating a fair humorous color. There are several varieties of folklore texts (or folklore texts) used by writers as a means of stylizing the animal element at fairs in Ukraine, as well as expressing the variety of socio-cultural masks presented to them (salesman, Jew, gypsy, blind musician, petitioner, gambler, etc.). It is emphasized that the concept of «fair» in the relevant narrative texts retains signs of burlesque and enlightenment. Particular attention is paid in the article to the fact that the texts of fair laughter culture are focused on the traditions of the «bottom», which contrast with the traditions of secular literature and culture in general, that is, the traditions of «the top». In analyzing the verbal imagery of the fair in prose works, it is taken into account that the basic techniques of creating a humorous color are the amplification of titles, actions, processes, as well as pun, the contractual blending of high into low, book and spoken, concepts related to the concept, «yourown – someoneelse’s».